1988
DOI: 10.1002/ana.410240109
|View full text |Cite
|
Sign up to set email alerts
|

Asymbolia for pain: A sensory‐limbic disconnection syndrome

Abstract: We describe the behavioral and neuroanatomical features of asymbolia for pain occurring in 6 patients following unilateral hemispheric damage secondary to ischemic lesions in 5 and traumatic hematoma in 1. In the absence of primary sensory deficits, these 6 patients showed a lack of withdrawal and absent or inadequate emotional responses to painful stimuli applied over the entire body, as well as to threatening gestures. Five patients also failed to react to verbal menaces. Patients appeared unconcerned about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
173
0
8

Year Published

1992
1992
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 378 publications
(189 citation statements)
references
References 29 publications
8
173
0
8
Order By: Relevance
“…Patients with insular cortical lesions have been reported to identify a noxious stimulus as painful but are unable to properly appreciate the meaning of their pain (48). Similarly, terminal cancer patients who have had prefrontal lobotomies appear to fully appreciate novel pain but exhibit diminished appreciation of the implications of their cancerrelated pain (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with insular cortical lesions have been reported to identify a noxious stimulus as painful but are unable to properly appreciate the meaning of their pain (48). Similarly, terminal cancer patients who have had prefrontal lobotomies appear to fully appreciate novel pain but exhibit diminished appreciation of the implications of their cancerrelated pain (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, lesions to the dorsal portion of the ACC (dACC) (4) or insula (5) result in patients reporting that they are no longer bothered by painful stimulation even though they can still perceive it. Similarly, neuroimaging studies have shown that the dACC tracks the affective component of pain (6) and is closely correlated with perceived pain unpleasantness (7)(8)(9).…”
mentioning
confidence: 99%
“…Finally, and perhaps of the utmost signifi cance, the re representation of this pathway in the anterior insular cortex is crucial for subjective feelings of pain (or any other feeling) in humans [15][16][17][18][19] , and neither rodents nor monkeys seem to have a homologous structure. The inescapable truth is that pain in humans is indeed a subjective experience.…”
mentioning
confidence: 99%